If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -40 = x + -1y Reorder the terms: -40 + 3x = x + -1y Solving -40 + 3x = x + -1y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -40 + 3x + -1x = x + -1x + -1y Combine like terms: 3x + -1x = 2x -40 + 2x = x + -1x + -1y Combine like terms: x + -1x = 0 -40 + 2x = 0 + -1y -40 + 2x = -1y Add '40' to each side of the equation. -40 + 40 + 2x = 40 + -1y Combine like terms: -40 + 40 = 0 0 + 2x = 40 + -1y 2x = 40 + -1y Divide each side by '2'. x = 20 + -0.5y Simplifying x = 20 + -0.5y
| 4y*=28y | | -0.0625x^2+2x-10=0 | | 5x^3(54x^2+1)=0 | | (-7x)(8xy)= | | 6x+1.2=6x+.2 | | 5p-15p*=0 | | -17+m=8 | | 34x=1200 | | -24=-3u | | -0.0625x^2+2x+10=0 | | 3(4y+1)+5y=10 | | 4x+0.4=0.4 | | Y+-6y+-17=8 | | 81x-2x+2=90 | | 2p+4=p-16 | | -21+-15= | | 2x=45.49 | | 81x-2+2=90 | | 14+7.3=x+12.8 | | -8=u+9 | | 2+0.4y=0.4 | | 5t*=25t | | 7x+4xy=12 | | (7X+5)(2X-2U-3)=EQUATION | | 13s+1s+6s-6=14 | | (15lnx)-(lnx^13)=ln(7x+30) | | 50-3u=17 | | -3x+5=2x-25 | | 486+22n=30n+350 | | 5x^2+4x-12= | | 11p+-4p+-18p+-p-11p=-13 | | 2x+3.5(3)=1.5 |